Potentiometric determination of stability constants for ternary Vanadium(III) complexes with dipicolinic acid and the amino acids serine, threonine, methionine and phenylalanine/ Determinación potenciométrica de constantes de estabilidad para complejos de - Moreno, María; Araujo, Mary Lorena; Martínez, José Daniel; Brito, Felipe; Hernández, Yohar; Nunez, Nataly; Hernandez, Lino; del Carpio, Edgar; Rodríguez, Mildred; Lubes, Vito (Revista de la Facultad de Ingeniería UCV, 2019)
In this work, we present the results of the speciation of the ternary complexes formed between vanadium(III), dipicolinic acid (H2Dipic) and the amino acids serine (Ser, HL), threonine (Thr, HL), methionine (Met, HL) and phenylalanine (Phe, HL), in aqueous solution at 25.0(1)°C using 3.0 mol.dm-3 KCl as the ionic medium. The analysis of the potentiometric data using the least squares computational program LETAGROP, indicates the formation of the species [V(Dipic)(HL)]+, V(Dipic)(L), [V(Dipic)(L)(OH)]- and [V(Dipic)(L)(OH)2]2-, in the ternary V(III)-H2Dipic-Amino acids (HL) systems studied. The values of Δ log K’’ for ternary systems involving amino acids have been evaluated and discussed. The species distribution diagrams as a function of pH were briefly discussed. The spectrophotometric spectra were done in order to get a qualitative characterization of the complexes formed in aqueous solution, indicates that the dipicolinate is acting as a tridentade ligand and the complexes formed are all heptacoordinated.